EGFR-Targeted Immunotoxin Exerts Antitumor Effects on Esophageal Cancers by Increasing ROS Accumulation and Inducing Apoptosis via Inhibition of the Nrf2-Keap1 Pathway - Yun Yang; Ziyin Tian; Yanke Ding; Xiaojing Li; Ziheng Zhang; Liu Yang; Fangyu Zhao; Feng Ren; Rui Guo (Journal of Immunology Research)
Previously, we developed a novel EGFR-targeted antibody (denoted as Pan), which has superior antitumor activity against EGFR-overexpressed tumors. However, it shows marginal effect on the growth of esophageal cancers. Therefore, the variable region of Pan was fused to a fragment of Pseudomonas exotoxin A (PE38) to create the immunotoxin, denoted as Ptoxin (PT). Results indicated that PT shows more effective antitumor activity as compared with Pan both on EGFR-overexpressed KYSE-450 and KYSE-150 esophageal cancer cells, especially on KYSE-450 cells. Moreover, treatment of PT induces regression of KYSE-450 tumor xenografts in nude mice. Furthermore, we investigated the potential mechanism involved in the enhanced antitumor effects of PT. Data showed that PT was more potent in reducing the phosphorylation of EGFR and ERK1/2. More importantly, we for the first time found that PT was more effective than Pan in inducing ROS accumulation by suppression of the Nrf2-Keap1 antioxidant pathway, and then induced apoptosis in KYSE-450 esophageal cancer cells, which may partly explain the more sensitive response of KYSE-450 to PT treatment. To conclude, our study provides a promising therapeutic approach for immunotoxin-based esophageal cancer treatment.